Signal to noise ratio in nanoscale bioFETs - Mori, Carlos Augusto Bergfeld; Martens, Koen; Simoen, Eddy; Van Dorpe, Pol; Agopian, Paula Ghedini Der [UNESP]; Martino, João Antonio (Elsevier, 2022)
We experimentally demonstrate the use of electrolytically gated SOI pFinFETs employed as bioFETs for the detection of single-stranded DNA and evaluate their low-frequency noise in the range between 1 Hz and 100 Hz. Both channel length and overdrive voltage dependencies are analyzed, showing the best (i.e., highest) signal to noise ratio for the devices with their gates biased around the threshold voltage, with little to no dependence on the channel length.
Keywords: 1/f noise; BioFET; FinFET; ISFET